Thyroid Nodules in Severely Obese Patients: Frequency and Risk of Malignancy on Ultrasonography. (2nd January 2020) - de Siqueira, Raquel Andrade; Rodrigues, Ana Paula dos Santos; Miamae, Lucas Massao; Tomimori, Eduardo Kiyoshi; Silveira, Erika Aparecida
ABSTRACT: Background : We aimed to compare the thyroid ultrasonographic findings of severely obese versus nonobese individuals, and the frequency, characteristics, and risk of malignancy in detected nodules. Design : Case-control study including 67 adults with severe obesity (body mass index [BMI] ≥ 35 kg/m 2 ) and 67 nonobese controls (BMI < 30 kg/m 2 ). The participants underwent ultrasound evaluation of the thyroid and cervical subcutaneous tissue. The risk of malignancy in detected nodules was determined using the American Thyroid Association (ATA) 2015 and the Thyroid Imaging Reporting and Data System (TI-RADS) classifications. Fine-needle aspiration biopsy (FNAB) was performed in nodules for which the procedure was recommended according to the ATA-2015 or TI-RADS criteria, and the cytological evaluation followed the Bethesda classification. Results : The mean BMI values in the case and control groups were 47.0 ± 6.1 kg/m 2 and 22.8 ± 2.7 kg/m 2, respectively. There were no differences between groups regarding sex, age, total T3, and antiperoxidase (antiTPO) antibody positivity. When compared with controls, severely obese individuals showed a greater frequency of parenchymal hypoechogenicity (p = 0.042), cervical subcutaneous tissue thickness (p < 0.001), overall frequency of thyroid nodules (p = 0.038), and frequency of multiple nodules (p = 0.013). No significant differences were observed in terms of risk of nodular malignancy according to both the ATA-2015 and TI-RADS classifications in severely obese compared with nonobese individuals. Conclusions : Severely obese individuals ( versus nonobese controls) presented increased parenchymal hypoechogenicity and frequency of thyroid nodules on ultrasonographic evaluation. However, no significant differences were observed in terms of risk of nodular malignancy between both groups according to the ATA-2015 and TI-RADS criteria. Thus, ultrasonographic thyroid screening of severely obese individuals is not justified.